Development economics - development policies: Some remarks on concepts, applications and fallacies - Mustó, István (Competitio, 2004)
This is a brief summary of the development theories and policies of the last 5 decades. The neoclassic economic approach, dependency paradigm and the contemporary "post-modern" concepts and strategies are analyzed and commented with reference being made to the respective problems and fallacies. Development, so the conclusion, is a self-regulating process in complex open and dynamic socioeconomic systems that are not susceptible to planning but which are progressively improving their ability to manage their increasing complexity and the mechanisms to adjust to changing circumstances.